Time-dependent blood flow and oxygenation in human skeletal muscles measured with noninvasive near-infrared diffuse optical spectroscopies - Yu, Guoqiang; Durduran, Turgut; Lech, Gwen; Zhou, Chao; Chance, Britton; Mohler, 3rd, Emile R; Yodh, Arjun G (Journal of biomedical optics, 2005)
We have employed near-infrared optical methods to measure noninvasively the dynamics of muscle blood flow and oxygen saturation (StO2) during cuff occlusion and plantar flexion exercise. Relative muscle oxygen consumption (rVO2) was also computed from these data. Diffuse correlation spectroscopy provides information about blood flow, and diffuse reflectance spectroscopy provides information about blood oxygenation. Ten healthy subjects and one patient with peripheral arterial disease (PAD) were studied during 3-min arterial cuff occlusion of arm and leg, and during 1-min plantar flexion exercise. Signals from different layers (cutaneous tissues and muscles) during cuff occlusion were differentiated, revealing strong hemodynamic responses from muscle layers. During exercise in healthy legs, the observed approximately 4.7 fold increase in relative blood flow (rBF) was significantly lower than the corresponding increase in rVO2 (approximately 7 fold). The magnitudes of rBF and rVO2 during exercise in the PAD patient were approximately 1/2 of the healthy controls, and the StO2 recovery time was twice that of the controls. The hybrid instrument improves upon current technologies for measuring muscle responses by simultaneously measuring rBF and StO2. The instrument thus provides a method for evaluation of microcirculation and muscle metabolism in patients with vascular diseases.